INOVASI EDUKASI GIZI DIGITAL: TINJAUAN LITERATUR EFEKTIVITAS E-BOOKLET MP-ASI TERHADAP PENGETAHUAN IBU BALITA - Sekar Santi Kurniasih; Rike Setio Surya Bayu; Widyastuti Widyastuti; Selviana Selviana; Linda Suwarni (Zaitun : Jurnal Ilmu Kesehatan, 2026)
Nutritional problems in toddlers, including stunting, remain a major public health challenge in Indonesia, where one of the primary preventive strategies is the appropriate provision of complementary feeding (MP-ASI). However, mothers' knowledge regarding proper MP-ASI practices remains limited, while conventional educational media are often perceived as less engaging and practical. Advances in digital technology have encouraged the utilization of electronic-based educational tools, such as e-booklets, as an alternative approach to delivering nutritional information. This literature review aims to examine scientific evidence regarding the effectiveness of e-booklets in enhancing mothers' knowledge of MP-ASI. A literature search was conducted using the PICOS framework across the Google Scholar, PubMed, ScienceDirect, and GARUDA databases for articles published between 2021 and 2026, resulting in seven selected articles analyzed using a narrative synthesis method. The findings indicate that the implementation of e-booklets significantly increases mothers' knowledge of MP-ASI, while also positively impacting child-feeding attitudes and practices. The effectiveness of this digital medium is supported by its visual appeal, ease of access via smartphones, operational flexibility, and higher cost efficiency compared to printed media. Ultimately, this review provides a strong theoretical foundation demonstrating that innovative e-booklets have great potential as an effective digital nutrition education medium to optimize public nutritional literacy while supporting stunting prevention efforts in toddlers